Density gradient driven microinstabilities and turbulence in ASDEX Upgrade pellet fuelled plasmas. (24th August 2017) - Angioni, C.; Lang, P.T.; Manas, P.
Abstract: ASDEX Upgrade plasmas fuelled by pellets in the H-mode confinement regime are analyzed. The gyrokinetic code GKW is applied to calculate the microinstabilities which are predicted to be unstable in these plasmas. Two types of density gradient driven modes are found, outside and inside the pellet deposition location. The first mode is driven by a negative radial density gradient, and corresponds to the usual density gradient driven trapped electron mode instability, producing a large diffusive particle flux directed outwards, and becomes more unstable with increasing trapped particle fraction and with decreasing collisionality. The second is driven by a positive radial density gradient (that is, a locally hollow density profile) and is identified for the first time in this work. The instability is located in the proximity of the high field side of the poloidal cross section, and drives a diffusive particle flux directed inward. It is mainly produced by the non-adiabatic response of passing particles with low parallel velocities at high collisionality and it becomes more unstable with increasing passing particle fraction and increasing collision frequency. Nonlinear gyrokinetic turbulence simulations show that these instabilities can lead to saturated turbulence and produce particle diffusion at experimentally relevant levels. In contrast to the usual behavior of the turbulent fields in tokamak plasmas, which have largest fluctuations on the low field side, locally hollow density profiles are prediced to lead to turbulent electrostatic potential and density fluctuations which are maximum on the high field side of the torus.